The Impact of Accountability Mechanisms on Public Sector Environmental Sustainability Performance: A Case Study of Sri Lanka - Keshara de Silva; Prem W. Senarath Yapa; Gillian Vesty (Australasian Accounting, Business and Finance Journal, 2020)
Asia is the fastest growing economic region that has attracted significant economic and infrastructure development. With increasing development, this region has become one of the main environmental polluters with significant environmental degradation, reduced water and air quality, and imperilled biodiversity. Traditional international donor and funding agencies such as the World Bank and Asian Development Bank have strict environmental safeguard policies drawn from Sustainable Development Goals, to ensure borrowing countries and projects comply with environmental sustainability. However, with an increasing shift to non-traditional donors such as China, environmental safeguards are not a key priority in developmental projects. The public sector plays a significant role in ensuring environmental sustainability and accountability, and is increasingly being pressured to revisit their concept of sustainability. Robust public sector accountability frameworks are paramount to achieve environmentally sustainable development. However, environmental sustainability research in developing country context is limited, public sector research is even scarce. This paper aims to fill this gap by clarifying the concept of environmental accountability of public sector entities in pursuing internationally funded development projects in Sri Lanka as a fast developing country in the south Asian region. This further analyses the roles and responsibilities of public sector agencies in relation to the environmental sustainability practices and the impact of international development funding agencies, including donor agencies on public sector accountability. The analysis indicates that despite the existing environmental sustainability guidelines and principles set by international agencies, environmental degradation continued to be a significant challenge in the country.
Keywords: Accountability; Environment; Sustainability; Public Sector; Sri Lanka; Developing country; Asia